Inflammatory markers and incident frailty in men and women: the English Longitudinal Study of Ageing. - Gale, C; Baylis, D; Cooper, C; Sayer, A (2013)
Cross-sectional studies show that higher blood concentrations of inflammatory markers tend to be more common in frail older people, but longitudinal evidence that these inflammatory markers are risk factors for frailty is sparse and inconsistent. We investigated the prospective relation between baseline concentrations of the inflammatory markers C-reactive protein (CRP) and fibrinogen and risk of incident frailty in 2,146 men and women aged 60 to over 90 years from the English Longitudinal Study of Ageing. The relationship between CRP and fibrinogen and risk of incident frailty differed significantly by sex (p for interaction terms <0.05). In age-adjusted logistic regression analyses, for a standard deviation (SD) increase in CRP or fibrinogen, odds ratios (95% confidence intervals) for incident frailty in women were 1.69 (1.32, 2.17) and 1.39 (1.12, 1.72), respectively. Further adjustment for other potential confounding factors attenuated both these estimates. For an SD increase in CRP and fibrinogen, the fully-adjusted odds ratio (95% confidence interval) for incident frailty in women was 1.27 (0.96, 1.69) and 1.31 (1.04, 1.67), respectively. Having a high concentration of both inflammatory markers was more strongly predictive of incident frailty than having a high concentration of either marker alone. In men, there were no significant associations between any of the inflammatory markers and risk of incident frailty. High concentrations of the inflammatory markers CRP and fibrinogen are more strongly predictive of incident frailty in women than in men. Further research is needed to understand the mechanisms underlying this sex difference.